Pentingnya Keterlibatan Aktif OMK Dalam Hidup Menggereja Di Rayon IV Paroki Salib Suci Nias Barat - Evimawati Harefa; Antonius P Sipahutar; Felisati Hulu (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Based on the initial observations of researchers in carrying out Week End Pastoral (WEP), OMK in Rayon IV Parish of the Holy Cross of West Nias, was very lacking in giving themselves to be involved in church life activities. This is caused by the development of technology that continues to grow and the freedom of parents towards their children. This study aims to find out who OMK is and to find out the active involvement of OMK in church life in Rayon IV West Nias Holy Cross Parish. This study uses a qualitative method. Qualitative research is research that describes social phenomena in accordance with the context that produces descriptive data in the form of written or spoken words from humans and from observable behavior. So through this method the researcher wants to see the overall phenomenon that occurs at the research location. The results of the researchers found that OMK were not actively involved, because parents and local church officials did not pay attention to providing opportunities to be involved in church life. Finally, OMK find their own comfort by freely roaming everywhere, playing online games, sports, and work.